A experiência do centro de informações toxicológicas (CIT) de Belém na intoxicação por chumbinho (carbamato) no período de março de 1998 a março de 2005 - LIMA, Maurício Batista (2022)
The carbamate poisoning constitutes a serious problem of public health, particularly in the developing countries, where there is a deficiency in the fiscalization and the control of the access to the toxic for the population. The present work aims to describe the clinical and epidemiologic profile of the patient victims of poisoning for carbamate notifying to the CIT - Belém in the period from March of 1998 to March of 2005. 408 records of notification of accidents for carbamate had been revised and 271 corresponded to the cases of poisoning for carbamate in the city of Belém in the mentioned period. Of the 7687 cases registered in the cited period, 5% of the notifications had corresponded the poisonings for carbamato. The majority of the cases occurred in proper capital (66%) and the remain (34%) in other cities. The Guamá and Sacramenta’s neighborhood corresponded to 7,32% and 7,01% of cases of poisoning. The female was the most expressive sex representing 57% of the registered cases. The age group from 20 to 29 years old, being responsible for 28,7% of cases of poisoning, and the age group from 30 to 39 years old, represented a number of 26,5% cases. 72% of the poisonings occurred in the residence and the students group was involved in 41 cases. 54% of the cases had occurred during suicide attempts. It was verified presence of clinical manifestations in 92% of the patients who had had contact with the carbamate, which them had been distinguished sialorrhea, myosis and emesis that corresponded to 85%, 65% and 55% of the cases, respectively. 57% of the patients had evolved for cure and 6% for the death. The poisoning was the type of more common occurrence, happened in 94,09% of cases and in 5,53% of accidents the exposition to the toxic agent occurred only. It was observed that the oral way of absorption was involved in 97% of the cases. In 97,41% of accidents the type of exposition acute-only was present and 83,76% had needed hospitalization. These results show that poisonings for carbamate deserve more attention for the sanitary authorities and the responsible agencies for its fiscalization, mainly in the developing countries.